The World Needs to Better Understand China - Nawaz, Ahsan; Chaudhry, Naveed Iqbal (Advances in Social Sciences Research Journal, 2023)
Chinese people are working together to build the Chinese path to modernization in the new era. In their book China in Xi Jinping Era, some Chinese scholars convey the lessons learned from China’s peaceful development to the world. To build a human community with a shared future, Chinese scholars must continue introducing China to the world by shaping a reliable, admirable and respectable image of China. Thus, the world can better understand China.